Kriteria Pemilihan Urutan Babi yang Disukai Konsumen di Kota Denpasar, Provinsi Bali - Gardipa, I Gusti Agung Teguh; Antara, Nyoman Semadi; Sedana Yoga, I Wayan Gede (JURNAL REKAYASA DAN MANAJEMEN AGROINDUSTRI; Vol 7 No 4 (2019): DesemberDO - 10.24843/JRMA.2019.v07.i04.p14, 2019)
Bali has many traditional foods, the most popular traditional in Bali, sausage. This study aims to determine the criteria of the order of urutan product in the city of Denpasar, Bali and to find out the most priority characteristics among the criteria that have been determined against the order of urutan in the city of Denpasar, Bali. This study uses the AHP (Analytic Hierarchy Process) method. The results of this study indicate that the AHP Test on the criteria shows that the weighting of the five experts is included in the criteria consistently and it can be concluded that the most important criterion is the taste criteria, with score of 0.350. The most important criteria in the sub-criteria for taste are the spicy sub-criteria, with score of 0.505. The most important criterion in the sub-criteria in the process is the sun criteria sub-criteria, with a score of 0.329. The most important criteria in the sub-criteria for the composition are the fat meat sub-criteria, with a score of 0.622. The most important criteria in the sub-criteria at the price are the 80-90 sub-criteria with a score of 0.478. The most important criterion in the sub-criteria for texture is the soft sub-criteria which is a score of 0.758. Keywords: Urutan, AHP, fermentted sausage